The Issues of Judicial Independence in Indonesia in Contemplation of Islamic Law - Tomi Agustian; Habiburrahman Habiburrahman; Rama Aryanda (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The judiciary (judicial) is an autonomous power that is unaffected by other authorities, especially the executive branch (president). However, the central to the author's analysis is the establishment of justice with the realization of an independent judicial power as the 1945 Constitution's ideals.